THE ROLE OF ENDOTHELIAL DYSFUNCTION IN THE DEVELOPMENT OF HEMOSTATIC DISTURBANCES IN RHEUMATOID ARTHRITIS AND IMPROVING TREATMENT STRATEGIES - Baxtiyorovna, Musayeva Nargiza (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This article investigates the role of endothelial dysfunction in the development of hemostatic disturbances and cardiovascular complications in rheumatoid arthritis (RA) patients. It aims to understand how RA-induced inflammation leads to endothelial dysfunction, increasing oxidative stress, and disrupting the blood clotting system, which heightens the risk of thrombosis and cardiovascular diseases. Methods: The study reviews existing literature and current treatment strategies, including biological therapies, anticoagulants, and anti-inflammatory agents, to explore their impact on reducing endothelial dysfunction and improving cardiovascular outcomes in RA patients. Results: The findings demonstrate that endothelial dysfunction, as a result of RA-induced inflammation, contributes to oxidative stress and disturbances in the blood clotting system. These factors collectively elevate the risk of thrombosis and cardiovascular diseases in RA patients, which are leading causes of morbidity and mortality. Novelty: This article highlights emerging therapeutic approaches that may provide better management of endothelial dysfunction and hemostatic disturbances in RA, offering new potential strategies for improving patient outcomes beyond current treatment options.